PREVENTIVE EFFECT OF LONG ACTING Β2-AGONISTS ON STATIN INDUCED MYOPATHIES: Β2-Agonists on Statin Induced Myopathies - Qamar, Abdullah; Butt, Shahdab Ahmed; Iqbal, Toqeer Ahmad (Pakistan Armed Forces Medical Journal, 2018)
Objective: To identify the histological effectsof statin-induced skeletal muscle myopathy in a Rat model and to find protective effect of long acting β2-agonists. Study Design: Laboratory based experimental randomized controlled trial. Place and Duration of Study: Study was conducted at the department of Anatomy, Army Medical College Rawalpindi in collaboration with National Institute of Health (NIH) Islamabad and Armed forces institute of Pathology (AFIP) Rawalpindi, from Jan 2015 to Jun 2016. Material and Methods: Adult male Sprague-Dawley rats were procured from NIH Islamabad. Their average approximate age was 70-80 days and weight range was 250 ± 50 grams. The animals were randomly selected and divided into three groups. Group A was the control. Each rat of group B received Simvastatin dissolved in distilled water, by oral gavage (60mg/kg/day) once daily, for 12 weeks. Animals of group C received simvastatin dissolved in distilled water, (60mg/kg/day) once daily plus formoterol dissolved in distilled water (3μg/kg/day) once daily for 12 weeks. Both were administered with the help of oral gavage. The animals were sacrificed after three months of the experimental period. Extensor digitorum longus (EDL) tendon was isolated and dissected out. Tissue processing was done on the EDL muscle followed by Haematoxylin and Eosin staining. Fiber crosssectional areas, Number of myofibers and Central Myonuclei were counted per high power field in each specimen of all three groups. Results: Examination of H&E stained sections of the extensor digitorum longus muscle of the control group revealed the histological structure of skeletal muscle. Cross sectional area of myofibers and number of myofibers were significantly lower in group B as compared to the control group A. Group C showed significant increase in cross sectional area of myofibers and number of myofibers as compared to group B. No central myonuclei was seen in any section. Conclusion: Simvastatin induced the histomorphological changes in the skeletal muscle of experimental rats by reducing myofiber size and number. Formoterol co-administration minimized simvastatin induced myopathy by significantly increasing myofiber size and number.